Further evidence of spontaneous cure in human Chagas disease Uma nova evidência de cura espontânea em doença de Chagas humana - João Carlos Pinto Dias; Emmanuel Dias; Olindo M. Filho; Danielle Vitelli-Avelar; Dalmo Correia; Eliane Lages; Aluízio Prata (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
An acute case of Chagas disease was studied in 1944, with clinical and laboratory follow-up until 2007, in Bambuí, Minas Gerais, Brazil. A five-year-old girl living in a rural hut that was highly infested with Triatoma infestans presented a febrile clinical condition compatible with the acute form of trypanosomiasis. She presented a positive thick blood smear, but never again showed serological and/or parasitological evidence of Trypanosoma cruzi infection, on several occasions. This patient never received any specific treatment and, to this day, she remains completely asymptomatic, with normal findings from clinical, electrocardiographic, X-ray and echocardiographic examinations. Um caso agudo de doença de Chagas foi estudado em 1944, com seguimento clínico e laboratorial até 2007, em Bambuí, Minas Gerais, Brasil. Vivendo em rancho rural altamente infestado por Triatoma infestans, e apresentando um quadro clínico febril compatível com forma aguda da tripanossomíase, uma menina de cinco anos teve gota espessa positiva, nunca mais apresentando evidências sorológicas ou parasitológicas de infecção pelo Trypanosoma cruzi, em variadas oportunidades. A paciente nunca foi tratada especificamente e permanece, até o presente, completamente assintomática, com exames clínicos eletrocardiográficos, radiológicos e ecocardiográficos normais.